Pulmonary Right Ventricular Resynchronization in Congenital Heart Disease: Acute Improvement in Right Ventricular Mechanics and Contraction Efficiency. (September 2017) - Janoušek, Jan; Kovanda, Jan; Ložek, Miroslav; Tomek, Viktor; Vojtovič, Pavel; Gebauer, Roman; Kubuš, Peter; Krejčíř, Miroslav; Lumens, Joost; Delhaas, Tammo; Prinzen, Frits
Abstract : Background—: Electromechanical discoordination may contribute to long-term pulmonary right ventricular (RV) dysfunction in patients after surgery for congenital heart disease. We sought to evaluate changes in RV function after temporary RV cardiac resynchronization therapy. Methods and Results—: Twenty-five patients aged median 12.0 years after repair of tetralogy of Fallot and similar lesions were studied echocardiographically (n=23) and by cardiac catheterization (n=5) after primary repair (n=4) or after surgical RV revalvulation for significant pulmonary regurgitation (n=21). Temporary RV cardiac resynchronization therapy was applied in the presence of complete right bundle branch block by atrial-synchronized RV free wall pacing in complete fusion with spontaneous ventricular depolarization using temporary electrodes. The q-RV interval at the RV free wall pacing site (mean 77.2% of baseline QRS duration) confirmed pacing from a late activated RV area. RV cardiac resynchronization therapy carried significant decrease in QRS duration ( P <0.001) along with elimination of the right bundle branch block QRS morphology, increase in RV filling time ( P =0.002), pulmonary artery velocity time integral ( P =0.006), and RV maximum +dP/dt ( P <0.001), and decrease in RV index of myocardial performance ( P =0.006). RV mechanical synchrony improved: septal-to-lateral RV mechanical delay decreased ( P <0.001) and signs of RV dyssynchrony pattern were significantly abolished. RV systolic stretch fraction reflecting the ratio of myocardial stretching and contraction during systole diminished ( P =0.001). Conclusions—: In patients with congenital heart disease and right bundle branch block, RV cardiac resynchronization therapy carried multiple positive effects on RV mechanics, synchrony, and contraction efficiency. Abstract : Supplemental Digital Content is available in the text.